Write2Engage: e-guidebook for beginner / Noorain Mohd Nordin ... [et al.] - Mohd Nordin, Noorain; Wei, Loon Koe; Jantan, Mohd Jefary; Md Taib, Norraeffa; Husain, Nor Azmawati (Universiti Teknologi MARA, Kedah, 2023)
Social media is one of the platforms that getting important in e-commerce world. It is an effective way for business to promote their product and services, reach new and existing customers. Write2Engage is an electronic guidebook designed for social media users, entrepreneurs, marketer, and student at the beginning level. Write2Engage is still new in the market, especially in rural areas. Furthermore, the existing e-guidebook are complicated and not attractive. Therefore, Write2Engage is created as an edutainment guiding tool for social media users, entrepreneur, marketer, and student to obtain some information regarding preparation of copywriting in social media. The main objective of Write2Engage is to develop knowledge and skill in preparing copywriting. In addition, it also eases the process of developing copywriting. In terms of its novelty, it comes with notes, video, animation, and interactive activities. The benefits of this product are: i) it is easy to learn and use ii) it builds skills in preparing copywriting iii) it helps to attract customers through good copywriting iv) increase the use of social media for marketing purposes. It is suitable to be used as a guidebook for beginner to explore social media in marketing their product effectively especially in IR 4.0 era.